Exploring IT professionals’ intention to use software development risk assessment framework - Darehshori, Elnaz Farhang (World Scientific and Engineering Academy and Society, 2013)
The paper builds on the Theory of Reason Action(TRA) and Technology Acceptance Model (TAM)to develop a research model in exploring information technology (IT) professionals’ intention to use a risk assessment framework in the context of software development. A total of 150 survey questionnaires were distributed on a convenient basis to Malaysian IT professionals in a software company; 106 were received. Out of this number, only 100 were used for analysis. There is evidence to suggest the application of TRA and TAM in explaining the intention to use a risk assessment framework in Malaysian software development environment. Other implications and future areas for research are discussed herein.